Baby Corn A wonder crop - Sharma, Arpita; Joshi, Deepa; Soni, Pooja Gupta; Bhat, Archana (Indian Farming, 2017)
Baby corn serves as a dual purpose crop and has potential to uplift farmerâ€™s socio-economic condition as it fetches handsome amount in the market but also provides year round green fodder that serves as nutritious feed for animals. Â